Uncovering origins of heterogeneous superconductivity in La3Ni2O7 - S. V. Mandyam; E. Wang; Z. Wang; B. Chen; N. C. Jayarama; A. Gupta; E. A. Riesel; V. I. Levitas; C. R. Laumann; N. Y. Yao (Nature, 2026)
Abstract The family of nickelate superconductors have long been explored as analogues of the high-temperature cuprates 1–6 . Nonetheless, the recent discovery that certain stoichiometric nickelates superconduct up to high critical temperatures ( T c ) under pressure came as a surprise 7–13 . The mechanisms underlying the superconducting state remain experimentally unclear. Apart from the practical challenges posed by working in a high-pressure environment, typical samples exhibit anomalously weak diamagnetic responses, which have been conjectured to reflect inhomogeneous ‘filamentary’ superconducting states 7,9,14–17 . Here we perform wide-field, high-pressure, optically detected magnetic resonance spectroscopy to image the local diamagnetic responses of as-grown La 3 Ni 2 O 7 samples in situ, using nitrogen vacancy quantum sensors embedded in the diamond anvil cell 18–23 . These maps confirm marked inhomogeneity of the functional superconducting responses at the few μm scale. By spatially correlating the diamagnetic Meissner response with both the local tensorial stress environment, also imaged in situ, and stoichiometric composition, we show the dominant mechanisms suppressing and enhancing superconductivity. Our wide-field technique simultaneously provides a broad view of sample behaviour and excellent local sensitivity, enabling the rapid construction of multi-parameter phase diagrams from the local structure–function correlations observed at the sub-μm pixel scale.